Academic Exam Reminder Information System for Information Technology Master Student in UUM - Chaki, Moussa Omar Mohammed (2009)
The master students need to take final examinations almost every subject. The time, venue and date of the exams are decided by the Academic Affair Department in Higher Education Academy (HEA). Students need to get the information of the exams from the lecturers; this action troubled lecturers a lot. Then the students need to remember the information by themselves, wait to the date of exams and go there without any reminder. Once a student miss the exam, he is likely to fail the subject and need to retake it in next semester, all the effort he made in this semester will be useless, everything need to start from zero in the next semester. In order to avoid this case which will waste the lecturers' and students' time and effort, a prototype to remind the students take their own exams on time is very necessary, this prototype is hoped to solve the miss of the exams.